2007
DOI: 10.4028/www.scientific.net/amm.10-12.444
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Assembly System for Large-Scale Complex Products

Abstract: Due to complex process and high difficult operation for large-scale products assembly, the application of virtual assembly (VA) has an important significance and also an actual value. In this paper the key techniques of VA for large-scale complex products are proposed, and their assembly characteristics (such as their organization form, human participation, process planning and optimization and so on) are analyzed. First, a new virtual environment (VE) system considering human activities is set up. Second, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…As large-scale products are usually linked to high investment, the suppliers produce their parts in time to ensure small storage property and a closely linked supply chain. Therefore a perfectly timed supply chain is required in the assembly process [10].…”
Section: Characteristics and Challenges In The Assembly Of Large-scal...mentioning
confidence: 99%
“…As large-scale products are usually linked to high investment, the suppliers produce their parts in time to ensure small storage property and a closely linked supply chain. Therefore a perfectly timed supply chain is required in the assembly process [10].…”
Section: Characteristics and Challenges In The Assembly Of Large-scal...mentioning
confidence: 99%
“…Up until the 2000s to 2010s, the ability to deploy the 3D product model to the assembly process was limited by software availability [4,5]. More recently, the following enabling factors have been removing these limitations [6] via transforming the engineering bill of materials (eBOM) into the manufacturing bill of materials (mBOM) [7][8][9]: the advent of manufacturing process management (MPM) systems [10], the ability to extract 3D product model data [11][12][13][14][15][16], and the growth in virtual manufacturing knowledge [17,18]. Building on these enabling factors, research has Eng 2024, 5 demonstrated that the 3D product model can be integrated with assembly line balancing via process consumption [19], can be used as the link between the bill of process (BOP) and the bill of materials (BOM) [20,21], and can check the product's configuration for assemblability [22].…”
Section: Introductionmentioning
confidence: 99%
“…As such feasibility came to fruition, researchers and industry alike have found ways to transform the engineering Bill of Materials into the Manufacturing Bill of Materials [6][7][8]; develop manufacturing process management software [9]; and extract 3D product model data and transfer it to virtual manufacturing and assembly software [10][11][12][13][14][15]. Researchers and industry also advanced this virtual assembly knowledge further, developing tools to automate assembly planning for complex products [16,17].…”
Section: Introductionmentioning
confidence: 99%